Pengaruh Latihan Dribbling With Cone dan Reverse The Ball Dribble Terhadap Peningkatakan Hasil Dribbling pada Klub Putra Anjani FC - M. Kalfika Atma; Soemardiawan Soemardiawan; Ismail Marzuki (Jurnal Porkes, 2026)
The problem addressed in this study is the low dribbling ability of Putra Anjani FC players, as evidenced by an average dribbling time of 18.48 seconds and the fact that more than 70% of players failed to dribble effectively when facing pressure from opponents. The purpose of this study was to examine the effects of “dribbling with cones” and “reverse the ball dribble” training and to compare the effectiveness of these two methods. The study employed a quantitative experimental design using a pretest-posttest control group design. The sample consisted of 30 players divided into two groups: Group A (dribbling with cones training) and Group B (reverse the ball dribble training). Training was conducted for 6 weeks, 3 times per week. The test instrument used was Morton’s dribbling test (Aiken’s V = 0.89; ICC = 0.91). The results showed that both training methods had a significant effect (p < 0.05). Group A experienced a reduction in completion time from 18.45 seconds to 12.32 seconds (a 33.2% improvement; g-score = 0.72), while Group B’s time decreased from 18.52 seconds to 14.78 seconds (a 20.2% improvement; g-score = 0.48). An independent samples t-test revealed a significant difference between the two groups (p = 0.001; Cohen’s d = 1.43). The conclusion of this study is that the “dribbling with cones” exercise is more effective than the “reverse ball dribble” exercise in improving the dribbling performance of Putra Anjani FC players.